Socio-economic Structure (Global Journal of Human-Social Science, 2023)
The main aim of this research is to determine how to develop sustainable development for the Munda community based on their current socio-economic structure in view of their current condition The study is mainly quantitative in nature Koira and Dumuria upazilas of Khulna district and Shyamnagar Debhata and Tala upazilas of Satkhira district were selected through convenient sampling techniques for the purpose of collecting primary data because a large part of the Munda community lives in these areas A structured questionnaire was used to collect data from 250 respondents from five preselected areas The respondents were selected using a simple random sampling technique The data was analyzed in terms of statistical indicators of frequency and percentage The results of the study show that social indicators economic indicators and cultural factors are very weak among the Munda community Among the social indicators Munda women and men have very little interest in following hygiene rules sanitation birth control Economic indicators show income sources and job opportunities The Munda community has been facing many challenges recently Many educated boys and girls in the Munda community spend their days in agony due to a lack of suitable jobs which has a negative impact on everyone in the community Cultural factors show that the Munda community which is plagued by poverty can celebrate its cultural events in a grand manner so that other communities or ethnic groups do not get any idea about their culture This research will be of great help to those who work with the indigenous communities of Bangladesh especially the various ministries of the government NGOs policymakers and government and private research organizations
Keywords: socio-economic; sustainable development; munda community; indigenous society